Agroecology Living Labs in the "South - Muntenia" and "South-East" development regions in Romania (identification, classification, characterization) - Ion Toncea; Aurora Ranca; Tudor Stanciu; Vladimir Adrian Toncea; Steliana Rodino (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 14th Edition, 2023)
The paper refers to the identification and classification of Living Agroecological Laboratories (ALL) and the selection of the most relevant ALL- Organic in the South-Muntenia and South-East development regions of Romania in 2021. Hypotetically, an Agroecology Living Laboratory should be any organic certified farm according to regulations of organic farming of IFOAM & European Comission. Based on the information provided by the "Ecological Agriculture" Department and the website of the Romanian Ministry of Agriculture and Rural Development, as well as in accordance with the concept and categories of business models from the RUBIZMO Horizon project (G.A. 773621, 2018-2021) and classification of farming systems, in this paper is presented: Type and number of operators: farmers, aquaculture producers, food and feed processors, traders, importers, exporters, collectors of wild flora and livestock and beekeepers, as well as the crops and livestock species and their area, respectively animals number in ecological agriculture identified in each county of the studied development regions; The ALL-Organic business models representative of "South-Muntenia and "South-East" regions in Romania 2021;
Keywords: O11; O12; 330; Agroecology Living Labs (ALL-Organic); development regions; business model